The Use of a Shared Services Model for Mycobacteriology Testing: Lessons Learned. (January 2018) - Stafford, Cortney; Atkinson-Dunn, Robyn; Buss, Sarah N.; Dalton, Tracy; Gibson, Debbie; Johnston, Stephanie; King, Ewa; Grace Lin, Shou-Yean; Mitchell, Kara K.; Murtaugh, William A.; Sease, Heather; Southern, Timothy R.; et al.
Objectives: Public health laboratories (PHLs) provide essential services in the diagnosis and surveillance of diseases of public health concern, such as tuberculosis. Maintaining access to high-quality laboratory testing is critical to continued disease detection and decline of tuberculosis cases in the United States. We investigated the practical experience of sharing tuberculosis testing services between PHLs through the Shared Services Project. Methods: The Shared Services Project was a 9-month-long project funded through the Association of Public Health Laboratories and the Centers for Disease Control and Prevention during 2012-2013 as a one-time funding opportunity to consortiums of PHLs that proposed collaborative approaches to sharing tuberculosis laboratory services. Submitting PHLs maintained testing while simultaneously sending specimens to reference laboratories to compare turnaround times. Results: During the 9-month project period, 107 Mycobacterium tuberculosis complex submissions for growth-based drug susceptibility testing and molecular detection of drug resistance testing occurred among the 3 consortiums. The median transit time for all submissions was 1.0 day. Overall, median drug susceptibility testing turnaround time (date of receipt in submitting laboratory to result) for parallel testing performed in house by submitting laboratories was 31.0 days; it was 43.0 days for reference laboratories. The median turnaround time for molecular detection of drug resistance results was 1.0 day (mean = 2.8; range, 0-14) from specimen receipt at the reference laboratories. Conclusions: The shared services model holds promise for specialized tuberculosis testing. Sharing of services requires a balance among quality, timeliness, efficiency, communication, and fiscal costs.